LA PRODUCCIÓN DE CONTENIDOS AUDIOVISUALES EN ULTRA ALTA DEFINICIÓN (UHD): EXPERIENCIA INMERSIVA EN EL VISIONADO MULTIMEDIA EN PANTALLAS TV Y SMARTPHONES - Dr. Francisco Javier MONTEMAYOR RUIZ,Dr. Miguel Ángel ORTIZ SOBRINO (Fonseca, Journal of Communication, 2023)
This research analyzes the production of audiovisual content in ultra high definition (UHD) as a catalyst factor of the new narratological discourse implanted in the media to the expressive, interactive and immersive possibilities obtained with the use of UHD 4K and 8K for viewing on large screen and, especially, in the ’fourth screen’. Through indepth interviews with experts from the academic and professional media world it is to establish an overview of the convergence of technology and industry of content creation, where the products are evolving to as for the entertainment needs of digital natives and adapting to new forms of consumption across multiple platforms, facing, in this way, a new business model for both industry technology industry and for the entire audiovisual sector.